A Systematic Review of New Trends in Ionic Liquids Applied to Electrolytes on Polysaccharides - Ornaghi, Heitor Luiz; Kerche, Eduardo Fischer; Neves, Roberta Motta; Monticeli, Francisco Maciel [UNESP]; Agnol, Lucas Dall (MDPI, 2022)
Polysaccharides are formed by a long chain of monosaccharides, with the main function of promoting energetic and structural reserves for plants and animals. They can be applied as a base of electrolytes, using ionic liquids (ILs) as a solvent base. The study of electrolytes is an emerging field, as they are applied as secondary batteries, fuel cells, solar cells, supercapacitors and chemical sensors. They operate stably under extreme conditions, maintaining their high thermal stability. Furthermore, their low cost and environmentally safe character, compared to conventional electrolytes, have attracted considerable attention in the scientific field. ILs are composed entirely of ions and could be potentially applied as solvents. As electrolytes, ILs are environmentally friendly, and their use in combination with polysaccharides leads to a synergic effect. In the present study, a systematic review was performed of all papers published from 2014 to 2022 regarding ILs and polysaccharides through a search of three databases. Due to the large number of results found, only papers about electrolytes were considered and the main findings described. This study allows for easy identification of the most relevant fields of study with respect to ILs and polysaccharides, as well as the main gaps to be explored in the literature.
Keywords: electrolytes; ionic liquids; solvent media; systematic review